The Subcellular Localization of the Receptor for Platelet-Activating Factor in Neutrophils Affects Signaling and Activation Characteristics - Emil Andréasson; Karin Önnheim; Huamei Forsman (Clinical and Developmental Immunology)
The localization in neutrophils, of the receptor for platelet-activating factor (PAFR), has been determined using subcellular fractionation and a receptor mobilization protocol. We show that the PAFR is expressed primarily in the plasma membrane. Although activation of neutrophils by PAF induces responses typical also of agonists that bind the formyl peptide receptors (FPR), known to be stored in mobilizable organelles, some quantitative as well as qualitative differences were observed when neutrophils were activated through these receptors. PAF is equipotent to fMLF (high affinity agonist for FPR1) to cleave off L-selectin and to induce granule/vesicle secretion but is more potent than fMLF to induce a rise in intracellular Ca2+. Similar to fMLF, PAF induced also a robust release of reactive oxygen species, but with higher EC50 value and was less sensitive to a PI3K inhibitor compared to the fMLF response. Despite the lack of a granule localized storage pool of receptors, the PAF-induced superoxide production could be primed; receptor mobilization was, thus, not required for priming of the PAF response. The desensitized PAFR could not be reactivated, suggesting that distinct signaling pathways are utilized for termination of the responses triggered through FPR1 and PAFR.